Penerapan Strategi Active Learning Tipe True or False Untuk Meningkatkan Keaktifan Belajar PAI Siswa Kelas VI SD Negeri 015 Pangkalan Tampoi - Faridah, Faridah (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This research purpose was to determine the application of true or false acitve learning strategy to increase the students ‘activeness in islamic education subjectat sixth grade SD Negeri 015 Pangkalan Tampoi. This type of research was classroom action research (CAR). The subject of the research was 29 students of sixth grade SD Negeri 015 Pangkalan Tampoi consisted of boys and 18 girls. From the results of the class action research and discussion were based on the research steps: 1) Planning for class action preparation, 2) Action implementation, 3) Observation, 4) reflection. This research was conducted in three cycles and each cycle was conducted in one meeting. In order to ensure the classroom action research, run well, the researcher arranges the steps: 1) action planning/preparation, 2) action implementation, 3) observation, and 4) reflection. The results showed that the application of the true or false acitve learning strategy increased the students ‘activeness in islamic education. The observations result of student learning activities in the class where data was taken reveled that in the first cycle the percentage of student activity was 54.54%, which indicated that the student activity was in the low category. In cycle 1, there was an increase in the percentage of learning activities to 63.64%. Between cycle I and cycle 2 there was an increase of 9.1%, although activity in cycle 2 was still in the low category. Therefore, the researchers returned to reflect, find obstacles, and find solutions to be applied to the next cycle. Student activity from cycle 2 to cycle 3 increased in 18.18%, in cycle 2 student learning activity was 63.64% and in cycle 3 it became 81.82%. Student activities in cycle 3 was already in the high category